2017
DOI: 10.1038/s41598-017-15294-9
|View full text |Cite
|
Sign up to set email alerts
|

Resistance monitoring and cross-resistance role of CYP6CW1 between buprofezin and pymetrozine in field populations of Laodelphax striatellus (Fallén)

Abstract: Monitoring resistance and investigating insecticide resistance mechanisms are necessary for controlling the small brown planthopper, Laodelphax striatellus. The susceptibility to four common insecticides of L. striatellus collected from Jiangsu, Anhui, Zhejiang and Jilin provinces of China in 2015 was monitored. The results showed that all field populations remained susceptible to chlorpyrifos and thiamethoxam with resistance ratios (RRs) of 2.3- to 9.5 and 1.6- to 3.3, respectively, while the insects had deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Metabolism experiments in vitro confirmed that BtCYP6CM1 can metabolize not only imidacloprid, but also hydroxylate pymetrozine 25,26 . In the small brown planthopper, there was cross‐resistance between pymetrozine and buprofezin, and knocking down LsCYP6CW1 could reduce resistance of Laodelphax striatellus to both 36 . However, expression of NlCYP6CW1 in Drosophila did not affect its susceptibility to pymetrozine (Table 2).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Metabolism experiments in vitro confirmed that BtCYP6CM1 can metabolize not only imidacloprid, but also hydroxylate pymetrozine 25,26 . In the small brown planthopper, there was cross‐resistance between pymetrozine and buprofezin, and knocking down LsCYP6CW1 could reduce resistance of Laodelphax striatellus to both 36 . However, expression of NlCYP6CW1 in Drosophila did not affect its susceptibility to pymetrozine (Table 2).…”
Section: Discussionmentioning
confidence: 95%
“…In addition, the whitefly BtCYP6CM1 has been reported to metabolize pymetrozine, and so we chose UAS‐BtCYP6CM1 as a positive control 25 . LsCYP6CW1 was overexpressed in pymetrozine‐resistant strain of Laodelphax striatellus , and knocking down LsCYP6CW1 significantly increased susceptibility to pymetrozine, 36 so we also constructed UAS ‐ NlCYP6CW1 to verify whether it is involved in pymetrozine resistance. Candidate P450 genes were expressed in Drosophila using the GAL4 / UAS system under the control of the Actin ‐ GAL4 driver, and then we calculated the Drosophila climbing score to determine its susceptibility to pymetrozine.…”
Section: Resultsmentioning
confidence: 99%
“…A series of P450s in CYP3 and CYP4 clades are induced or overexpressed in planthoppers and involved in the metabolism of insecticides, such as CYP4CE1 , CYP6AY1, and CYP6CW1 [ 9 , 10 , 11 ]. Metabolic resistance mediated by the P450s has been considered as the dominant factor for insecticide resistance in the field populations of planthoppers [ 12 , 13 , 14 ]. A previous study showed that the genetic variants of CYP2E1 and CYP1A1 resulted in the susceptibility to chronic Hepatitis B virus infection [ 15 ], suggesting P450s in CYP3 and CYP4 clades might be involved in the regulation of virus infection.…”
Section: Introductionmentioning
confidence: 99%
“…Imidacloprid is a representative neonicotinoid insecticide and can disturb the nervous system of insects [ 10 , 11 ], while deltamethrin is a modulator of nerve sodium channels in insects [ 24 ]. Pymetrozine is a fast-acting and selective inhibitor of the feeding of sap-sucking insects [ 14 ]. Buprofezin is an insect growth regulator and can interfere with metabolism and inhibit chitin synthesis in insects [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation